Fighting HIV/AIDS: is success possible? - Okware, Sam; Opio, Alex; Musinguzi, Joshua; Waibale, Paul (Bulletin of the World Health Organization, 2001)
The fight against HIV/AIDS poses enormous challenges worldwide, generating fears that success may be too difficult or even impossible to attain. Uganda has demonstrated that an early, consistent and multisectoral control strategy can reduce both the prevalence and the incidence of HIV infection. From only two AIDS cases in 1982, the epidemic in Uganda grew to a cumulative 2 million HIV infections by the end of 2000. The AIDS Control Programme established in 1987 in the Ministry of Health mounted a national response that expanded over time to reach other relevant sectors under the coordinating role of the Uganda AIDS Commission. The national response was to bring in new policies, expanded partnerships, increased institutional capacity for care and research, public health education for behaviour change, strengthened sexually transmitted disease (STD) management, improved blood transfusion services, care and support services for persons with HIV/AIDS, and a surveillance system to monitor the epidemic. After a decade of fighting on these fronts, Uganda became, in October 1996, the first African nation to report declining trends in HIV infection. Further decline in prevalence has since been noted. TheMedical Research Council (UK) and the Uganda Virus Research Institute have demonstrated declining HIV incidence rates in the general population in the Kyamulibwa in Masaka Districts. Repeat knowledge, attitudes, behaviour and practice studies have shown positive changes in the priority prevention indicators. The data suggest that a comprehensive national response supported by strong political commitment may be responsible for the observed decline. Other countries in sub-Saharan Africa can achieve similar results by these means. Since success is possible, anything less is unacceptable.
Keywords: Acquired immunodeficiency syndrome/prevention and control/epidemiology/therapy; HIV infections/ prevention and control/epidemiology/therapy; National health programs; Health care reform; Knowledge; Attitudes; Practice; Behavior therapy; Intersectoral cooperation; Sentinel surveillance; Uganda (source: MeSH )